Urban heat mitigation effect and affordable housing greenery injustice measured by Green View Index (GVI): A case study in Washington, D.C. - Zhang, Zhenpeng; Fang, Fang; Greenlee, Andrew; Lou, Jiankun (AESOP, 2024)
The deterioration of living conditions is highlighting the benefits of urban greenery for creating sustainable cities. Using Washington D.C. as a case, we demonstrate the performance of GVI and examine disparities in greening surrounding affordable housing. With the pre-trained segmentation model, we generated GVI based on 54,691 Street View images and applied the Spearman's correlation analysis to examine LST cooling effect. We found that LST shows significant negative correlations (p<0.001) with GVI and newly developed GVI-3D with coefficients of -0.60 and -0.73. The distribution of GVI in residential zoning was polarised, affordable housing projects have less greenery. In conclusion, we argue that it is of practical significance to monitor GVI instead of large scale NDVI for urban environments due to its controllability and human-centric attributes. Keywords: Green View Index, Temperature mitigation, Street greenery, Housing environment, Environmental justice
Game changer? Planning for just and sustainable urban regions, Paris, 8-12th July 2024